2009
DOI: 10.1021/ac900504s
|View full text |Cite
|
Sign up to set email alerts
|

New Strategy for the Screening of Lysosomal Storage Disorders: The Use of the Online Trapping-and-Cleanup Liquid Chromatography/Mass Spectrometry

Abstract: The aim of this study was to set up a robust method suitable for large-scale studies (screening) with a minimized preparation process and with reduced running costs, for measuring five enzyme activities on dried blood spots by a new and simplified tandem mass spectrometry-based method. After incubation, all 5 reaction mixtures, carried out separately, were stopped, combined together, and centrifuged. The cleaning-up of the injected mixture was performed through a fast online trapping step preceding a liquid ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 47 publications
0
70
0
1
Order By: Relevance
“…An experienced operator can perform the cleanup of 4,500 samples, the daily workload of an average size screening laboratory, within 4-6 h. Recent introduction of online HPLC sample cleanup technology would save the time-consuming cleanup procedure as well as consumables but requires longer analysis time (LaMarca et al 2009) or more sophisticated equipment (Kasper et al 2010). However, using online HPLC cleanup on MS/MS, the instrument very likely can be used only for LSD screening and is blocked for other analysis.…”
Section: Discussionmentioning
confidence: 99%
“…An experienced operator can perform the cleanup of 4,500 samples, the daily workload of an average size screening laboratory, within 4-6 h. Recent introduction of online HPLC sample cleanup technology would save the time-consuming cleanup procedure as well as consumables but requires longer analysis time (LaMarca et al 2009) or more sophisticated equipment (Kasper et al 2010). However, using online HPLC cleanup on MS/MS, the instrument very likely can be used only for LSD screening and is blocked for other analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The first such protocol was described in a report by la Marca et al (24 ), in which they suggested that online multidimensional HPLC sample preparation eliminated the need for laborious preanalytical steps with the use of a homebuilt multidimensional LC method in which a POROS cleanup column (Applied Biosystems) and an analytical C18 column were used.…”
Section: Discussionmentioning
confidence: 99%
“…A multiplex tandem mass spectrometry (MS/MS) assay for five LSDs (KD, Gaucher, Pompe, Niemann-Pick, and Fabry diseases) was developed 13 and optimized for use on dried blood spots. 15,18,19 There are challenges to adding LSDs to NBS panels, including the need for expensive instrumentation and adequate quality control materials (especially dried blood spots from infants with KD), 14,20 diagnostic laboratories for confirmatory testing with short turnaround times, infrastructure for rapid referral and urgent transplantation in newborns with EIKD, protocols for follow-up, and clinicians experienced in interpreting and relaying the full spectrum of NBS results, including variability in enzyme activity and identification of sequence variants of unknown significance or variable expressivity. 21 Early studies showed that a small cohort of infantile KD patients who received umbilical cord blood transplantation from unrelated donors prior to symptom onset had preserved neurological function.…”
mentioning
confidence: 99%